Akuntabilitas Pengelolaan Aset Tetap Pemerintah Daerah : (Studi Kasus Bpkad Kota Surabaya) - Moch Iqbal Romadhon; Muhammad Taufiq Hidayat (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This survey evaluates the responsibilities related to fixed asset management of the Surabaya City Regional Financial Asset Management Agency (BPKAD) based on the Ministry of Home Affairs Regulation No. 19 of 2016. This study adopts a descriptive qualitative approach through detailed observation, interviews, and document analysis. The analysis focuses on the five main steps of municipal asset management: planning, implementation, operation, reporting, and accountability. The survey results indicate that digital systems such as SIMBADA, SIGASDA, E-SIMKOD, and SIPGAD contribute to improving the transparency of audit histories and maintaining audit records. All stages are generally carried out in accordance with existing regulations. Nevertheless, there are still several unresolved issues, including limitations in human resource capacity within the regional office (OPD), discrepancies between the condition of physical assets and recorded data, and technical problems during the reporting period. Clear regulations, the digitization of systems, and oversight by external agencies such as the Audit Board of Indonesia (BPK), the Corruption Eradication Commission (KPK), and the Ministry of Home Affairs strengthen accountability. Overall, accountability has been achieved, although improvements in system optimization and human resource competence remain necessary.